Differences in rhizosphere soil fungal communities of wild and cultivated Paeonia ludlowii species - Qiao, Hongyong; Gao, Danlei; Yuan, Tao (Frontiers in Plant Science, 2023)
Introduction Paeonia ludlowii is a rare and endangered plant species with a high application value. However, its low cultivation success rate in China has severely limited its protection, development, and utilization. In addition to natural factors, microorganisms in the rhizosphere play an important role in determining its cultivation success. Methods In this study, growth indexes and soil physicochemical properties of both wild (origin: Nyingchi) and cultivated (introduction: Luanchuan) species of P. ludlowii were measured during the flowering, fruiting, and autumn foliage stages. ITS high-throughput sequencing technology was employed to detect rhizosphere soil fungi, and the diversity, community structure, functional prediction, molecular network, and ecological processes of the microbial community assembly were examined by multidirectional analysis. Results and discussion The results indicated that: both wild and cultivated P. ludlowii species were able to flower and fruit normally, although the wild species had a higher number of flowers and fruits and higher soil available phosphorus and available potassium contents than those of the cultivated species. Ascomycota and Basidiomycota were the dominant rhizosphere soil fungal phyla in both P. ludlowii species. However, our network analysis showed that Ascomycota as the key fungal phylum of the wild species, whereas the cultivated species lacked key fungi. The community assembly mechanisms of rhizosphere soil fungi in both wild and cultivated species were primarily stochasticity, with no significant differences between them. Based on the results of FUNGuild and molecular network analyses, cultivated species had a higher proportion of fungi, such as Soil Saprotroph, that can easily cause diseases. Additionally, the network connections among fungi were weaker in the cultivated species than those in the wild species, which increased the cultivated species susceptibility to external environmental interferences. Therefore, from a soil microorganism perspective, this study suggests that, after the introduction and cultivation of P. ludlowii, if rhizosphere soil fungi fail to gradually form a close network relationship and instead promote the growth of pathogenic fungi, the fungal ecosystem would become vulnerable.